2014
DOI: 10.1021/ef500478b
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Chemical Composition of the Halophyte Salicornia bigelovii under Cultivation

Abstract: Straw of the halophyte Salicornia bigelovii was chemically analyzed for lignocellulosic components, extractives, and ash in relation to varying cultivation conditions (namely, irrigating water salinity and fertilizer grade). Irrigation water contained 10−50 ppt salt, and fertilizer application varied between 1 and 2 gN/m 2 . Composition of the biomass was comparable to traditional lignocellulosic biomasses, containing glucan (up to 27 g/100 g total solids (TS)), xylan (up to 23 g/100 g TS), and lignin (24 g/10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
5
15
0
Order By: Relevance
“…Moreover, the stem fractions of Salicornia bigelovii contained less structural ash, 2-8%, as compared to its seed spikes, 5-14%. Conclusively, stems contained less ash both on the surface and incorporated in the plant matrix when compared to pods [76,78].…”
Section: Ash Contentmentioning
confidence: 88%
See 4 more Smart Citations
“…Moreover, the stem fractions of Salicornia bigelovii contained less structural ash, 2-8%, as compared to its seed spikes, 5-14%. Conclusively, stems contained less ash both on the surface and incorporated in the plant matrix when compared to pods [76,78].…”
Section: Ash Contentmentioning
confidence: 88%
“…This is reflected in findings from Turcios et al [73] and Turcios et al [74], where cultivating halophytes under different salinity showed an increase in both crude ash and structural ash content with increasing salinity. As stated in Cybulska et al [76], a large portion of initial ash content in the raw Salicornia bigelovii plant was in the form of extractable ash, as irrigating the biomass with saline water showed more salt deposits on the plant surface than being incorporated within the plant matrix. Moreover, the stem fractions of Salicornia bigelovii contained less structural ash, 2-8%, as compared to its seed spikes, 5-14%.…”
Section: Ash Contentmentioning
confidence: 90%
See 3 more Smart Citations